The Effect of Self-Efficacy, Competence, Work Discipline, Employee Engagement on Work Performance and Work Motivation: Empirical Study on Umrah Travel Agency - Didin Sjarifudin; Tri Widyastuti; Istianingsih; Sugeng Suroso (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of the research to be conveyed is to find the influence between the variables in this paper between independent variables and dependent variables. This study used a survey method. Testing the proposed hypothesis involves the use of statistical expressions or structural models suitable for causal analysis. Therefore, the method used in this study is a quantitative approach with correlational research, which is a type of research that aims to find out whether there is a relationship between several variables (Cooper and Schlinder, 2006). The population in this study is employees of Umrah travel agencies from several Umrah bureaus in Jakarta, Bekasi, Depok, a population of 37 employees with purposive Sampling, Data Analysis Techniques using simple regression analysis assisted by SPSS version 25